Dynamics of Non-Linear Student Motivation in Choosing the MPI Study Program at the Postgraduate Program at UIN Maulana Malik Ibrahim Malang - M. Irsyad Maulana; Munirul Abidin (Khalifah : Jurnal Pendidikan Nusantara, 2024)
This study emphasizes the dynamics driving non-linear students to choose the Management of Islamic Education (MPI) program at the Postgraduate School of UIN Maulana Malik Ibrahim Malang. Often, these students lack a clear understanding of their reasons for selecting this program of study. Employing a qualitative descriptive approach involving in-depth interviews, the research explores the intrinsic and extrinsic motivational components influencing this decision. The findings indicate that students' personal interests, familial encouragement, career aspirations, and the influence of the academic environment shape their motivation. Hence, non-linear student motivation stems from a combination of internal factors, such as personal ambition and the need for self-development, and external factors, including family support and inspiration from successful individuals. Optimism, utilization of academic resources, and effective time management are additional factors driving adaptation within the academic environment. This provides program managers with practical insights to enhance their support for non-linear students.